Estudo do fenômeno de exchange bias em bicamadas NiFe/IrMn e tricamadas NiFe/IrMn/Co - Sousa, Marcos Antonio de (2013)
This work reports the study of the phenomenon of exchange bias in NiFe/IrMn bilayers and NiFe/IrMn/Co trilayers. In the NiFe/IrMn bilayers, ferromagnetic resonance experiments at X and Q bands microwave frequencies reveal that spin wave and NiFe resonance modes are excited by the oscillating microwave field. Angular variations of the absorption fields in the plane of the films for both resonance modes shows the effect of the unidirectional anisotropy field, whose intensity is twice larger for the spin wave mode, due to an additional contribution of an unidirectional surface anisotropy. The experiments also indicate the presence of a uniaxial anisotropy of the NiFe layer, apparently dependent on the applied magnetic field. The magnetic parameters of both resonance modes were deduced considering a generalized phenomenological model which also includes the contribution of a rotatable anisotropy. In the NiFe/IrMn/Co trilayers, the angular variations of the resonance field in the plane of the films reveal the effect of the unidirectional anisotropy field for both independent resonance modes of NiFe and Co layers. The ferromagnetic resonance results combined with magnetometry data show that the exchange bias phenomenon at the NiFe/IrMn interface influences the same phenomenon at the IrMn/Co interface, and that this effect must be mediated by a spiral structure of spins across the IrMn antiferromagnetic layer. For both systems studied, the values of the exchange bias field deduced from the ferromagnetic resonance experiments are consistent with the values given by magnetization measurements.